Neonatal Pain Management - Heath, Nicola (2008)
Throughout history the main focus within neonatology has been the survival of neonates. They receive numerous procedures essential for their survival. However the pain control for these lifesaving procedures was and still is forgotten and mistreated. Due to the 20 year history of debate and controversy about the existence and management of neonatal pain it has taken years to fully establish that neonates feel painful stimuli. There are obvious immediate, short-term consequences of repetitive painful stimuli but the long-term consequences may be more sinister. More pertinent consequences are being raised such as; altered development of the immature brain and pain system caused by repetitive noxious stimuli.